Research on End-to-End Delay Performance Based on GPS Scheduling System - Wang Yang; Zhou Jin-he; Ye Keng (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper summarizes some results of network calculus. It derives the bounds on end-to-end delay and effective bandwidth by network based on leaky bucket regulators. The simulation results show that the network calculus is a good fit for calculating end-to-end delay. And it provides effective control, scheduling and management in the integration network conditions in the following step. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5474